2014
DOI: 10.1016/j.bpj.2013.11.3593
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Neurotoxin II Provides Adaptivity of its Functional Sites

Abstract: Phosphorylation by cAMP dependent Protein Kinase A (PKA) is a ubiquitous signaling enzyme that regulates a variety of cellular functions. The regulatory and the catalysis subunits of PKA exist as a holoenzyme in an inactive state until cAMP releases the catalytic subunit (PKA-C). PKA is the prototypical kinase and has served as a benchmark for allosteric signaling in kinases. Previous work has demonstrated that binding of the nucleotide to PKA-C acts as a dynamic activator for the kinase, who's structural dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…590 Similar to the smaller toxins discussed above, it was found that membrane binding of α-neurotoxin facilitates its delivery to the receptor, in a study combining NMR spectroscopy and MD simulation. 591 In particular, specific interactions with the anionic DOPS lipids promoted a specific "standing" orientation of α-neurotoxin on the membrane suitable for receptor inhibition. 591 Interestingly, cardiotoxins are structurally homologous to neurotoxins but confer less toxicity and are believed to interact with intracellular components in addition to membrane targets.…”
Section: Membrane-bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…590 Similar to the smaller toxins discussed above, it was found that membrane binding of α-neurotoxin facilitates its delivery to the receptor, in a study combining NMR spectroscopy and MD simulation. 591 In particular, specific interactions with the anionic DOPS lipids promoted a specific "standing" orientation of α-neurotoxin on the membrane suitable for receptor inhibition. 591 Interestingly, cardiotoxins are structurally homologous to neurotoxins but confer less toxicity and are believed to interact with intracellular components in addition to membrane targets.…”
Section: Membrane-bindingmentioning
confidence: 99%
“…591 In particular, specific interactions with the anionic DOPS lipids promoted a specific "standing" orientation of α-neurotoxin on the membrane suitable for receptor inhibition. 591 Interestingly, cardiotoxins are structurally homologous to neurotoxins but confer less toxicity and are believed to interact with intracellular components in addition to membrane targets. MD simulations have been used to explore membrane association modes and membrane penetration mechanisms for cobra cardiotoxin CTX A3.…”
Section: Membrane-bindingmentioning
confidence: 99%